Kepadatan penumpang KRL dan kenyamanan komuter dalam mobilitas Perkotaan Jakarta - rafa nur fatihah; Sujarwo; Setyowati Rini Riris (Dimensia: Jurnal Kajian Sosiologi, 2026)
The need for an effective transportation system has made the Commuter Line the primary mode of daily travel for Jakarta residents. Population growth and urban activities have led to increased passenger density, reflecting an urban mobility crisis. This study aims to analyze KRL congestion as a reflection of urban mobility issues and its impact on passenger comfort. The study focuses on the level of KRL congestion and its implications for user travel experiences. This study uses a descriptive qualitative approach with data collection techniques in the form of literature studies and the researcher's empirical experience as a KRL user in Jakarta. The results show that KRL congestion causes physical discomfort, psychological stress, and a decrease in travel quality. These findings confirm that KRL congestion is part of the structural challenges of urban mobility that require public transportation planning oriented towards user comfort.